Calorimetric measurement of energy and nutrient stimulation of microorganisms from the continental deep subsurface - Feyhl-Buska, Jayme; Wu, Fabai; Smith, Isaiah E.; LaRowe, Douglas E.; Robador, Alberto; Kruger, Brittany; Osburn, Magdalena R.; Amend, Jan P. (Frontiers in Microbiology, 2024)
Microbial activity in the deep continental subsurface is difficult to measure due to low cell densities, low energy fluxes, cryptic elemental cycles and enigmatic metabolisms. Nonetheless, direct access to rare sample sites and sensitive laboratory measurements can be used to better understand the variables that govern microbial life underground. In this study, we sampled fluids from six boreholes at depths ranging from 244 m to 1,478 m below ground at the Sanford Underground Research Facility (SURF), a former goldmine in South Dakota, United States. The heat produced by microorganisms in these samples was measured in a nanocalorimeter as a proxy for activity. Heat flow measurements on unamended groundwater samples from five of the six boreholes comprising the Deep Underground Microbial Observatory (DeMMO) fell below the limit of detection, suggesting very low metabolic rates. Fluid samples from the borehole that registered a heat signal (DeMMO 6) from 1,478 m deep, were amended with a series of electron donors, electron acceptors, and amino acids before being introduced into the calorimeter. The addition of formate resulted in more than a ~500 nW increase in heat flow relative to the signal for unamended fluids during the first 100 h of incubation while the next highest heat flow arose from nitrate and acetate co-addition, at ~125 nW. Notably, both amendment conditions led to a ~1.5 orders of magnitude increase in cell density without causing major changes to community composition, suggesting that these electron donors and acceptors may be exploited by these communities in-situ. The addition of ~0.4 mM casamino acids resulted in a total heat flow of 2.25 μW within 35 h and a more than three orders of magnitude increase in cell density. In these experiments, Hydrogenophaga grew to dominate the amino acid amended borehole fluids. The strong microbial response to amino acid addition indicates a deep continental surface community that is limited by the availability of amino acids. A high potential for amino acid metabolism was proposed in genomic studies from this and similar sites but has not been shown in actively growing communities.